A spontaneous mutation in MutL‐Homolog 3 (HvMLH3) affects synapsis and crossover resolution in the barley desynaptic mutant des10. Issue 3 (8th July 2016) - Colas, Isabelle; Macaulay, Malcolm; Higgins, James D.; Phillips, Dylan; Barakate, Abdellah; Posch, Markus; Armstrong, Susan J.; Franklin, F. Chris H.; Halpin, Claire; Waugh, Robbie; Ramsay, Luke
Summary: Although meiosis is evolutionarily conserved, many of the underlying mechanisms show species‐specific differences. These are poorly understood in large genome plant species such as barley ( Hordeum vulgare ) where meiotic recombination is very heavily skewed to the ends of chromosomes. The characterization of mutant lines can help elucidate how recombination is controlled. We used a combination of genetic segregation analysis, cytogenetics, immunocytology and 3D imaging to genetically map and characterize the barley meiotic mutant DESYNAPTIC 10 ( des10 ). We identified a spontaneous exonic deletion in the orthologue of MutL‐Homolog 3 ( HvMlh3 ) as the causal lesion. Compared with wild‐type, des10 mutants exhibit reduced recombination and fewer chiasmata, resulting in the loss of obligate crossovers and leading to chromosome mis‐segregation. Using 3D structured illumination microscopy (3D‐SIM), we observed that normal synapsis progression was also disrupted in des10, a phenotype that was not evident with standard confocal microscopy and that has not been reported with Mlh3 knockout mutants in Arabidopsis. Our data provide new insights on the interplay between synapsis and recombination in barley and highlight the need for detailed studies of meiosis in nonmodel species. This study also confirms the importance of early stages of prophase I for the control of recombination in large genome cereals.